Toward enhancing customer citizenship behaviors in service sector - Phan, Bích Phương (2020)
The customer citizenship behavior is a quite new topic for both theoritical research and emperical research. It is undeniable that, along with the development of service industry, it is more and more difficult for firm to enhance their competitive advantage. In this fast moving society, customer is considered as the important source forcompany not only because of the benefit comingfrom their frequence of consumption but also fromtheir contribution to organization as helping firm improve the service, increase firm’s reputation by their word of mouth,engage more new customersto use firm’s serviceby their recommendation, orby othertheir voluntary behaviorsto helpother customer discreationally